LIBERTATEA FEMEII ȘI IMPACTUL EI ÎN VIAȚA CLASICULUI UCRAINEANO-RUS NICOLAE GOGOL (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2024)
Women’s Freedom and its Impact on the Life of the Ukrainian-Russian Classic Nicholas Gogol.Women’s freedom and its impact on the life of Nicholas Gogol is a lesser known and almost unstudied subject. This article aims to highlight some of the essential elements of the impact women had on the life of the Ukrainian- Russian classic Nicholas Gogol. Throughout the lifespan, humans are influenced by those who surround them. Some people influence through support and encouragement, others disappointing and betraying their vulnerable victims. Regardless of the positive or negative aspect of the impact, each of them contributes to the formation of attitude, character, vision and of life in general. It is well known, looking at Gogol’s writings and his correspondence, that he was certain of the fact that a woman has a special influence in the society. Gogol draws attention and encourages women to respect God’s standards in demeanor, communication and image in general, in such a manner that their influence makes the world a better place. The present article will analyse the social circle of N. Gogol, concentrating on the image of the woman who is present in the writer’s life, the one who had an impact, in a way or another, over his writings and over his life, in general.